SPATIAL THINKING OF STUDENTS TECHNOLOGY OF USING THE GEOGEBRA MATHEMATICAL PACKAGE IN FORMING (EXAMPLE OF BODIES OF ROTATION) - Kuchkarova daughter of Dilnovaz Shaymakhammat (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, we show how to build graphs and create models of objects of rotation in three-dimensional space with the help of Geogebra special software for the formation of students’ spatial thinking. We used literature [4] and [5].